Analisis Penggunaan Gadget Terhadap Pola Komunikasi Keluarga - Herna Alifiani; Nurhayati Nurhayati; Yulia Ningsih (Faletehan Health Journal, 2019)
Indonesia is a country that ranks second in the world in the use of gadgets. The increasing number of users of gadgets in this modern era, many cause negative effects for humans, one of which is the decline in effective communication patterns between adolescents with parents. The purpose of this study is to determine the relationship between the use of gadgets to the pattern of communication with family on the students of class x in SMK Yabhinka Kota Cilegon. The cross sectional study design, the study was conducted in June 2018, and 77 respondents. The results showed that from 45 respondents with the use of gadget often there are 44 people (97,8%) that communication pattern with family is less good and 1 (2,2%) that communication pattern with good family. 32 respondents with the use of gadget sometimes there are 5 people (15,6%) that communication pattern with her family is not good and 27 people (84,4%) that communication pattern with her family is good. Based on the results of chi square test shows that the value of p = 0,000 (<0.05) and the value of OR (Odss Ratio) 237. The conclusion of the relationship between the use of gadgets to the pattern of communication with the family because it found a lot of respondents who misuse gadgets, namely addicted gadgets games during school hours), have individual soul, lack of effective communication, and interaction of all-needed gadgets as media.